2008
DOI: 10.1007/s10554-008-9392-3
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and safety of adenosine stress perfusion cardiovascular magnetic resonance imaging in patients with severe coronary artery disease

Abstract: We sought to assess the tolerance and safety of adenosine-stress cardiovascular magnetic resonance (CMR) perfusion imaging in patients with coronary artery disease (CAD). We retrospectively examined all adenosine CMR perfusion scans performed in our centre in patients with known or suspected (CAD) and normal volunteers at either 1.5 or 3 T. All subjects were initially screened for contraindications to adenosine. The dose of adenosine infused was 140 microg/kg/min. Significant CAD was defined angiographically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 18 publications
4
26
2
Order By: Relevance
“…All other side effects were infrequent. This number of subjective adverse events was low when compared to that of other studies, which reported mild symptoms such as flushing, breathlessness or chest discomfort in up to 45% (15) and 63% (18) of the subjects. This is probably due to the selected patient populations with severe coronary artery disease within those previous studies.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…All other side effects were infrequent. This number of subjective adverse events was low when compared to that of other studies, which reported mild symptoms such as flushing, breathlessness or chest discomfort in up to 45% (15) and 63% (18) of the subjects. This is probably due to the selected patient populations with severe coronary artery disease within those previous studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have been published on the adverse events of adenosine in the setting of CMR (15,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Affected coronaries fail to dilate properly resulting in a coronary steal phenomenon, manifested as a non-homogenous increase in coronary blood flow, which is reflected in the non-homogeneous distribution of the radio-isotope that can be mapped using a gamma-camera. Adenosine and ATP, and more recently a selective A2AR agonist (Lexiscan [458]), have been used as pharmacologic stressors in this setting [746][747][748][749][750][751][752][753][754]. The use of adenosine-cardiac magnetic resonance imaging for the detection of CAD has been recommended recently [755][756][757].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…A recent study examined the safety and tolerance of stress CMR in 351 subjects, but 46 of these were healthy, normal volunteers [5]. A current metaanalysis of 35 studies, which included 13-229 patients, revealed a high sensitivity of 89% but only a moderate specificity of 80% [6].…”
mentioning
confidence: 99%